Relações étnico-raciais e quilombos: dos conhecimentos socioculturais aos currículo da educação escolar quilombola na Amazônia paraense - ANDRADE, Simei Santos (Universidade Federal do Pará, 2021)
This study analyzes Ethnic-Racial Relations and socio-cultural knowledge in quilombola communities in Northeast Pará and its interface with the Quilombola School Education curriculum. The qualitative approach was used, a documentary study of the Pedagogical Political Project of schools that work in Quilombola School Education and photographs on the socio-cultural aspects of quilombola communities in Northeast Pará. We used discourse analysis based on Bakhtin's discursive dialogism ( 2010) and specialized bibliography on the subject. The results of the study reveal that the PPP presents a curriculum focused on Quilombola School Education, considering the specificities of the historical, political, economic and socio-cultural reality of the quilombo, being flexible and dialogical (school and local community). Sociocultural knowledge is recognized and valued by the community and strengthened by a solidarity network, which keeps the quilombo's history and culture alive through the knowledge of the elders, the knowledge of the land and ancestry. It is concluded that the PPP for the quilombola school community is constituted as an emancipatory project (which houses conflicts, struggles and resistance). The curricular proposal of Quilombola School Education incorporates traditional knowledge from communities in conjunction with school knowledge (without hierarchy) and seeks to organize knowledge and social and cultural practices, considering the presence of knowledge that circulates, dialogues and questions the social life of quilombos surveyed in the Amazon of Pará.